ANALISIS KETEPATAN TERAPI DAN KEPATUHAN KONSUMSI OBAT TERHADAP GLUKOSA DARAH PUASA PADA PASIEN DM TIPE II DI PUSKESMAS PEKUNCEN - Aziez Ismunandar; Luthfi Hidayat Maulana (Sekolah Tinggi Ilmu Kesehatan Borneo Lestari Banjarbaru, 2020)
The national prevalence of DM was 2.1% of the total population of 250 people in 2013.The prevalence of DM in 2013 in Central Java based on RISKESDAS was in 13th place,which was 1.9% of the total population of 24,084,433. In Banyumas Regency as much as 2, 2%. Meanwhile, in the city of Purwokerto there were 1992 cases of diabetes mellitus in2016. The aim of the study was to determine the effect of therapy adherence andmedication adherence to fasting blood gluosa in type 2 DM patients. type II DM patients.Data analysis using linear regression test. The results showed that 62.9% and 37.1% ofpatients with blood glucose levels were not reached and reached. Patients with therapyaccuracy and inappropriate categories were 45.7% and 54.3%. 68.6% of patients with highadherence. Multiple linear regression test shows the effect of the accuracy of oralantidiabetic drug therapy with fasting blood sugar levels in type II DM patients with a sigvalue. equal to 0.004. Conclusion There is an influence between the accuracy of oralantidiabetic drug therapy with fasting blood glucose at Pekuncen Health Center.